VIOLENCE AND MIGRATION IN THE WORLD DURING THE COVID 19 PANDEMIC PROCESS (Third Sector Social Economic Review, 2022)
The Covid 19 Pandemic has had significant effects on conflict and migration. While the pandemic affected all countries, its global and inter-system relations made it difficult to establish a common ground between the conflict parties. It has not been possible to achieve regional and global peace during the pandemic. The pandemic has had multifaceted and important consequences in terms of political, social and economic aspects. While there has been a decrease in the types of violence such as war and conflict throughout the world during the pandemic process, there has been an increase in the actions against civilians. Despite all the measures, especially social isolation, during the pandemic period, there has been an increase in the number of people migrating inside and outside the country. Countries with internal conflicts have spent a significant part of their material and moral energies, which they need to spend for national security, on the fight against the pandemic. This study is a descriptive research in survey model. The aim of the study is to examine the distribution and intensity of violence and migration events in the world during the pandemic. In the study, information about the current situation is given with maps, tables and graphics.
Keywords: Covid-19; Violence; Migration; Conflict; Geography